Evidence-based school leadership and management : a practical guide - Jones, Gary, 1961- (London : SAGE Publications Ltd, 2018)
There is a vast amount of research on what goes on in schools, but how can school leaders sort credible findings from dubious claims and use these to make informed decisions that benefit their schools? How can abstract ideas from research be translated into dynamic plans for action? This book is a practical guide to evidence-based school leadership demonstrating the benefits that can be gained from engaging with robust educational research and offering clear guidance on applying meaningful lessons to practice. Topics include: What is evidence-based school leadership and why does it matter? How to collect data from your own school and how to analyse this evidence in order to inform strategic leadership decisions Models for implementing school improvement and change Leadership skills for fostering a culture of evidence-based practice This is essential reading for senior and middle leaders in educational organisations who aspire to lead effective schools with high levels of staff well-being and enhanced outcomes for the learners they teach.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Educational leadership; School management and organization